Prevalence of gestational diabetes mellitus and associated factors among women receiving antenatal care at a tertiary hospital in South-Western Uganda - Kahimakazi, Irene; Tornes, Yarine Fajardo; Tibaijuka, Leevan; Kanyesigye, Hamson; Kiptoo, Joshua; Kayondo, Musa; Ngonzi, Joseph; Adu-Bonsaffoh, Kwame; Abesiga, Lenard; Lugobe, Henry Mark (The Pan African Medical Journal, 2023)
Introduction: gestational diabetes mellitus is one of the major causes of morbidity and mortality among pregnant women worldwide. We aimed to determine the prevalence and factors associated with gestational diabetes mellitus among women attending the antenatal care clinic at a tertiary care hospital in South-Western Uganda. Methods: this was a hospital-based cross-sectional study conducted among women at ≥24 weeks of amenorrhea attending the antenatal care clinic at Mbarara Regional Referral Hospital between December 2020 and March 2021. We screened all women for gestational diabetes mellitus using the World Health Organisation 2013 diagnostic criteria. We obtained socio-demographic, medical, and obstetric data. Multivariable logistic regression was used to determine the factors independently associated with gestational diabetes mellitus. Results: we enrolled 343 pregnant women with a mean age of 27.3 (SD ±12.3) years. Of the 343 participants, 35 (10.2%) had gestational diabetes mellitus (GDM) (95% C.I: 7.4%-13.9%) and 7 (2%) had diabetes in pregnancy. The factors significantly associated with gestational diabetes mellitus were; previous history of foetal macrosomia in any of the previous pregnancies (aOR: 5.53, 95% C.I: 1.2923.65) and family history of diabetes mellitus in the first-degree relatives (aOR: 4.45, 95% C.I:1.4813.34). Conclusion: one in every ten pregnant women attending the antenatal care clinic at Mbarara Regional Referral Hospital is likely to have gestational diabetes mellitus in pregnancy. There is a need to strengthen routine testing for gestational diabetes mellitus among women attending the antenatal care clinic, especially pregnant women with a prior history of foetal macrosomia and a family history of diabetes mellitus in first-degree relatives.
Keywords: Gestational diabetes mellitus; Antenatal care; Uganda; Pregnant women